Net energy metering scheme based on time of use pricing for residents in Malaysia - Abdul Hafiz Bin Razali (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The current Malaysia’s net energy metering (NEM) scheme has been updated in 2019 that credits excess generation into the next billing month at retail rate compare to at displaced cost. The new NEM may attract more installation of solar photovoltaic (PV) system among residential customers. However, it is discovered that customers with low monthly electricity consumptions are still not benefited since their electricity cost is lower than the PV generation cost. Implementing time-of-use (TOU) pricing on NEM scheme may overcome the problem as it based on hourly energy usage. This paper compares the annualized energy cost of residential PV system under different TOU prices and NEM scheme. The results show that an optimized TOU prices as suggested in this paper may give financial benefits to all residential customers with PV system, including the one with low monthly consumption.